Filosofía Educativa Personal y Devenir Ideológico: de la práctica individual al significado social - Alba Eugenia Vásquez-Miranda (Universidad de la Costa, 2021)
The writing of a teaching philosophy statement can be interpreted as a dynamic component in the development of the teacher's system of ideas, their ideological self. In this reflective article, the exercise of personal reflection and growth that promotes the development of a personal teaching philosophy is examined according to some available writing guidelines. Through a documentary method, the assumptions of the beliefs in question are argued in order to interpret them under the Baktinian concepts of heteroglossia and ideological becoming. The examination of heteroglossia in the text of a TPS increases the awareness of individual teaching activity connected to broader social, cultural, and political practices built through writing. These considerations are intended to connect the activities of educators with the possibility of more democratic societies.